2011
DOI: 10.4103/0189-6725.78671
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory laparotomy for acute intestinal conditions in children: A review of 10 years of experience with 334 cases

Abstract: The need for re-exploration not only increases the morbidity but also increases mortality as well. Diverting temporary ileostomy adds little cumulative morbidity to the primary operation and is a safe option for diversion in selected cases. The best way to further reduce the mortality is to create ileostomy at first operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
2
10
0
5
Order By: Relevance
“…13 It was the most common indication of laparotomy in paediatric patients and also forms an important cause of mortality and morbidity in them. 14,15 This similar type of study were carried out by Gangopadhyay et al in 765 cases, Park CH and Woo et al in 77 cases and Adeyemi D et al in 211 cases and they found male and female ratio was 2.3:1, 3.2:1 and 3:1 respectively while in present study, M:F ratio was 3:2 with higher female ratio as compared to other studies (Table 7). [16][17][18] Park CH and Woo et al also studied clinical features in their study in 77 paediatric patients with intestinal obstruction.…”
Section: Resultssupporting
confidence: 85%
“…13 It was the most common indication of laparotomy in paediatric patients and also forms an important cause of mortality and morbidity in them. 14,15 This similar type of study were carried out by Gangopadhyay et al in 765 cases, Park CH and Woo et al in 77 cases and Adeyemi D et al in 211 cases and they found male and female ratio was 2.3:1, 3.2:1 and 3:1 respectively while in present study, M:F ratio was 3:2 with higher female ratio as compared to other studies (Table 7). [16][17][18] Park CH and Woo et al also studied clinical features in their study in 77 paediatric patients with intestinal obstruction.…”
Section: Resultssupporting
confidence: 85%
“…In another report of 334 children (excluding neonates, atresias, anorectal malformations, Hirschsprung's disease, trauma and tumours) with peritonitis, [16] 44 (13.2%) required terminal ileostomy. Of 290 that did not have ileostomy, 28 (9.7%) needed re-exploration for anastomotic leak, burst abdomen or faecal fistula, while three (6.8%) of the ileostomy group needed to be re-explored.…”
Section: Discussionmentioning
confidence: 98%
“…A scoring system using characteristic physical findings, such as the Alvarado score, does not provide sufficient sensitivity and specificity for the diagnosis. Exploratory laparoscopy has been used as a diagnostic treatment 13 . Exploratory laparoscopy is also useful in terms of the transition to surgical treatment.…”
Section: Discussionmentioning
confidence: 99%